Komunikasi Interpersonal Pimpinan Tambuo dalam Mempertahankan Loyalitas Karyawan - Siti Sarah Andriani; Satya Candrasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Employees are one of the most substantial factors in the success of a company. For that, leaders must have a great interpersonal communication so that employees remain loyal to the company. A leadership role is needed to guide and direct employees. So, they can act according to what the company expects. This study aims to determine how the interpersonal communication of Tambuo leadership in maintaining employee loyalty. This research uses a qualitative approach with a descriptive study. Data collection techniques using observation, interviews, and documentation. The results showed that the leaders of Tambuo have a good interpersonal communication in increasing employee loyalty, by prioritizing the principles of kinship, openness, and tolerance. Communication is carried out using informal language while still upholding the value of politeness and mutual respect, so that it makes employees comfortable at work, has integrity, compliments each other on the performance of other employees, employees can be role models, and there is a constructive criticism for the organization. It is because the leadership is very receptive to input and suggestions from employees to improve the organization.